The CORRELATION OF BLOOD SUGAR LEVELS WITH THE ELASTICITY OF CORONARY ARTERIES - INDAH ROHMAWATI; Dora Dayu Rahma Turista (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2019)
Coronary arteries are blood vessels that carry oxygen and nutrients to the heart muscle. These vessels can experience constriction due to the accumulation of plaque which causes atherosclerosis. Atherosclerosis is characterized by reduced coronary artery elasticity. Blood glucose levels are one of the factors that cause atherosclerosis. The aims of this study was to determine whether there was a correlation of blood sugar levels with the elasticity of coronary arteries. This study is an analytical study with cross sectional design. The population in this study were all patients who visited the Gipateda Tulungagung treatment clinic that was more than 30 years old and female. Through accidental sampling technique, 30 respondents were obtained. The study was conducted from March 1, 2016 to May 1, 2016. Data was collected using a quantum resonance magnetic analyzer (QMRA) to determine the value of blood sugar levels and the value of elasticity of coronary arteries. The data obtained were analyzed statistically by bivariate linear regression tests to determine whether there was a significant correlation of blood sugar levels with the elasticity of coronary arteries. The results showed that the p value is 0.000 < 0.05, which means that there was a significant correlation between blood sugar levels and the elasticity of the coronary arteries. High blood glucose levels can damage the vascular endothelium and also increasing platelet agegrat, so that can resulting atherosclerosis. Every individual should be able to control blood sugar levels with a healthy lifestyle and early detection regularly to prevent the decrease of coronary arteries elasticity because that can lead to coronary heart disease (CHD).